Monitoring and risk assessment of pesticides in a tropical river of an agricultural watershed in northern Thailand - Sangchan W. (2014)
The increasing application of pesticides in the uplands of northern Thailand has increased the transfer of pesticides to surface water. To assess the risk of pesticide use for stream water quality, we monitored the concentrations of seven pesticides (atrazine, dichlorvos, chlorpyrifos, dimethoate, chlorothalonil, (α-, β-) endosulfan, cypermethrin) frequently used in the Mae Sa watershed (77 km2) in water and sediment samples over a period of one and a half years (2007-2008). All investigated pesticides were recorded in the river. Chlorpyrifos was detected most often in water samples (75 % at the headwater station), while cypermethrin was most often found in riverbed (86 %) and in all suspended sediment samples. The highest concentrations of the pesticides were detected during the rainy season. About 0.002 to 4.1 % by mass of the applied pesticides was lost to surface water. The risk assessment was based on the risk characterization ratio (RCR). The RCRs of dichlorvos in water, (α-, β-) endosulfan, and cypermethrin in water and sediments were higher than unity indicating that they are likely to pose a threat to aquatic ecosystem. Finally, we discuss the role of sampling design on ecotoxicological risk assessment. Our study shows that pesticide contamination of surface waters is an environmental issue in the Mae Sa watershed and that measures need to be undertaken to reduce the loss of pesticides from soil to surface waters. © 2013 Springer Science+Business Media Dordrecht.